ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA RUMAH MAKAN BEBEK FARANNISSA DI SITUBONDO - Wulandari, Wiji; Wiryaningtyas, Dwi Perwitasari; Syahputra, Hendra; Ciptasari, Ayu Dita Windra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of the research is to find out the Analysis of the Factors Influencing Purchase Decisions Through Consumer Satisfaction as Mediation Variables at Bebek Farannissa Restaurant in Situbondo. The sampling technique used is simple random sampling with a total sample of 98 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that taste has a positive and significant effect on consumer satisfaction, price has a positive and significant effect on consumer satisfaction, taste has a positive and significant effect on purchasing decisions, price has a negative and insignificant effect on decisions purchase, consumer satisfaction has a positive and significant effect on repurchase decisions, taste has a positive but not significant effect on purchasing decisions through consumer satisfaction, price has a positive and significant effect on purchasing decisions through consumer satisfaction